Price Dynamics of Crude Oil in the Short and Long Term - Benbachir, SaÃ¢d; Lembarki, Sihame (International Journal of Economics and Financial Issues, 2018)
The drop in the price of crude oil in 2014 left no one indifferent, and motivated several researchers to analyse the nature of the relationship between the physical and the financial market of this commodity. This article discusses the issue of Spot and Futures price dynamics of crude oil in the short and long term. The originality of the present work is that we will proceed to a double analysis of the stochastic processes of the two variables Spot and Futures - with and without break - for the period from February 2015 to December 2017, using the models VAR and VECM. This last allows to understand short-term price dynamics while the VAR makes it possible to understand it in the long term. The results obtained estimate that there is a bidirectional causality between the two variables, and that their long-term dynamics undergo the same changes together. The Spot and Futures prices hold the fall of their prices on the same date of January 2016 (common break date for the 2 series), which distinguishes between two sub-periods and consequently two distinct regimes: "Tension" and "return to the average" regime. In the short term, the first one cannot reject the theory of normal backwardation, while the storage theory reasonably explains the return to the path of the equilibrium of the prices of the oil markets. Keywords: Spot & Futures markets, Cointegration, Autoregressive vector model (VAR), Vector error correction model (VECM) JEL Classifications: C22, G15, Q41